Analisis Pemahaman Agama dan Etos Kerja Islami Terhadap Kinerja Civitas Akademika ITB Ahmad Dahlan - azhar, Nurlis; Fathurrahman, Aldi (Journal of Islamic Management, 2024)
This research examines the influence of religious understanding and Islamic work ethic on employee performance at ITB Ahmad Dahlan Jakarta. Religious understanding and Islamic work ethic are measured through Likert scales and analyzed using Partial Least Square (PLS). The results indicate that religious understanding and Islamic work ethic positively contribute to enhancing employee performance. The implications highlight the importance of attention to religious understanding and the application of Islamic work ethic to achieve optimal performance in the workplace. These findings have strategic implications for human resource development in similar organizations.